A Clinico-Pathological Correlation of Childhood Primary Nephrotic Syndrome in Jakarta - I. G. N. Wila Wirya (Indonesian Pediatric Society, 1993)
Three hundred and sixty-four out of 547 children with primary nephrotic syndrome (PNS) treated at the Department of Child Health, Medical School, University of Indonesia between January 1970 and December 1979, were biopsied. The clinical, laboratory, and pathological characteristics of these patients were evaluated and compared with those reported by the International Study of Kidney Disease in Children (ISKOC, 1978) comprising children of Western countries with PNS. Results of this study showed that the spectrum of the histopathological changes in the 2 study populations was slightly different. Clinical and laboratory characteristics of certain types of PNS also showed some differences compared with those of ISKDC report. Patients with non-minimal changes nephrotic syndrome (NMCNS) were more frequently found in this study, and they were older than those of ISKDC report, i.e., more children < 6 years of age were affected with this disease in Jakarta. Similarly, this study showed that patients with minimal changes nephrotic syndrome (MCNS) were older than those of ISKDC report; the peak age of Western patients was less than 6 years. Patients with focal segmental glomerulosclerosis (FSGS) and membranoproliferative glomerulonephritis (MPGN) reported by ISKDC were more severe than those of this study as far as clinical and laboratory characteristics were concerned. The causes of these clinical and histopathological discrepancies between the two studies need to be further elucidated.